2013
DOI: 10.1002/ajim.22162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Occupational Exposure to Aflatoxins on Some Liver Tumor Markers in Textile Workers

Abstract: Exposure to fungi had a significant effect on AFM1 measurements and tumor biomarkers, especially in allergic textile workers (with the exception of the arginase biomarker), though results were generally within normal limits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…21,26,27 Textile workers exposed to high concentrations of airborne Aspergillus flavus had significant elevations in the urinary AFM1; the metabolite of AFB1, and the liver tumor biomarkers AFP and AFU compared to a control group, although the tumor markers were generally within normal limits. 28 In the present study, the significant elevation of the serum AFU in the bakers compared to the flourmill workers and the normal controls reflects the high risk of this occupational group of developing HCC. This finding is confirmed by the significant correlation between AFU and AFB1/Alb in the bakers.…”
Section: Discussionsupporting
confidence: 45%
“…21,26,27 Textile workers exposed to high concentrations of airborne Aspergillus flavus had significant elevations in the urinary AFM1; the metabolite of AFB1, and the liver tumor biomarkers AFP and AFU compared to a control group, although the tumor markers were generally within normal limits. 28 In the present study, the significant elevation of the serum AFU in the bakers compared to the flourmill workers and the normal controls reflects the high risk of this occupational group of developing HCC. This finding is confirmed by the significant correlation between AFU and AFB1/Alb in the bakers.…”
Section: Discussionsupporting
confidence: 45%
“…This could be caused by the aflatoxin ability to determine the mutation of the p53 tumor suppressor gene, which in normal conditions induces the apoptosis processes [74][75][76][77] . The risk of HCC increases when the exposure occurs in the presence of HBV infection, as occurs in the Chinese population [78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96] .…”
Section: Aflatoxinsmentioning
confidence: 99%
“…A variety of chemicals comprising VCM, organic solvents, chlorinated pesticides and arsenic exert adverse effects on the liver [97] (Tables 2 and 3). [4,38,41,44] , waste operators [38,44] Group 1 [34] HCV -Health care workers [38,39,61] Group 1 [34] Aflatoxin B1 1162-65-8 Paper mill and sugar factory; poultry production; rice mill; waste management; swine industry; agri-food industry; wheat handling; textile manufacturing [77,78,[87][88][89][90][91]93,96] Group 1 [76] IARC: International Agency for Research on Cancer; CAS No. : Chemical abstract service number; HBV: Hepatitis B virus; HCV: Hepatitis C virus.…”
Section: Non-infective Risk Factors For Hepatocellular Carcinomamentioning
confidence: 99%
“…22 Viegas et al report occupational exposure to aflatoxin B1 in workers involved in poultry and swine production. 6,10 Hayes et al conducted a follow-up study on 71 Dutch oilpress workers exposed to aflatoxin primarily via the respiratory route and observed that the mortalities for total-cancer and respiratory cancer were higher than expected in the aflatoxin-exposed group.…”
Section: Discussionmentioning
confidence: 99%